Liberalism, Development, and Gender: Responses to Papers - Nussbaum, Martha C. (Columbia Journal of Gender and Law, 2010)
I must begin by warmly thanking all the people here at Columbia who made this Symposium possible. I feel immensely honored and grateful for all of the time the participants spent with my work and for their acute criticisms. I shall introduce my specific responses to the papers by saying something about the ways that gender and sexuality figure in my work over the years. Then, I shall move through the papers, grouping them by thematic sections, but considering each separately to some extent, because I really learned so much from each of them.